A study exploring the relationship between employee happiness and financial performance within a South African financial institution - Waugh, Geoffrey William (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
This research is an investigation of the relationship between employees 'happiness' and the financial performance of a financial services organisation in South Africa. As a component of the financial services industry the banking sector contributes greatly to the economic growth of the country. The South African Banking sector is concentrated and highly competitive. It is vital for banks to maintain competitiveness and ever increasing global competition adds further pressure on organisations to financially perform so as to meet the demands of their shareholders. The literature that has been reviewed and previous research suggest that employee 'happiness' is a vital variable influencing the performance and success of individuals. Organisational performance will be measured in terms of financial performance for the purposes of this research. The concept of financial performance and 'happiness' are discussed and a questionnaire based on the Satisfaction With Life Scale (Diener et al,1985) is used to determine the levels of 'happiness' at selected branches within the institution. The individual branches financial performance is determined via calculating selected ratios, namely cumulative leverage, cost to income ratio and net yield. An analysis of correlation was conducted to establish whether or not a relationship of statistical significance exists between employee 'happiness' and financial performance. It was concluded that there is no relationship of statistical significance between employee 'happiness' and the financial performance of branches within the organisation, it was suggested that other factors exert a much greater influence over financial performance. Some of these factors influencing financial performance are discussed and recommendations for further research are made.
Keywords: Financial institutions -- South Africa; Employee motivation; Financial institutions -- Ratings and rankings; Banks and banking -- South Africa; Bank employees -- South Africa; Job satisfaction